2017
DOI: 10.1242/jeb.160234
|View full text |Cite
|
Sign up to set email alerts
|

Chamber music – An unusual Helmholtz resonator for song amplification in a Neotropical bush-cricket (Orthoptera, Tettigoniidae)

Abstract: We use laser vibrometry, micro computed tomography and finite element modelling to show that an unusual pronotal inflation covering the wings of a bush-cricket acts as a Helmholtz resonator. AbstractAnimals use sound for communication, with high-amplitude signals being selected for attracting mates or deterring rivals. High amplitudes are attained by employing primary resonators in sound producing structures to amplify the signal (e.g., avian syrinx). Some species actively exploit acoustic properties of natura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…For example, in several species not only does the right mirror radiate sound but also the adjacent cells (the neck and the harp, Fig. a,b) exhibit high levels of deformation during resonant vibration (Montealegre‐Z & Postles, ; Chivers et al ., ; Jonsson et al ., ). In other species (e.g.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…For example, in several species not only does the right mirror radiate sound but also the adjacent cells (the neck and the harp, Fig. a,b) exhibit high levels of deformation during resonant vibration (Montealegre‐Z & Postles, ; Chivers et al ., ; Jonsson et al ., ). In other species (e.g.…”
Section: Discussionmentioning
confidence: 97%
“…Not surprisingly, males of these species tend to produce broadband calling songs (Morris & Pipher, , ; Pipher & Morris, ; Morris et al ., ; Heller, ; Jatho et al ., , ; Morris & Mason, ; Hemp et al ., ; Lemonnier‐Darcemont et al ., ). Even when the left stridulatory cell shows some levels of activity, high levels of mechanical asymmetry between both left and right wings are observed, with maximum amplitude exhibited by the right stridulatory area (Montealegre‐Z & Mason, ; Montealegre‐Z & Postles, ; Sarria‐S et al ., ; Chivers et al ., ; Jonsson et al ., ). This wing asymmetry seems to have been selected as a way to reduce acoustic interference between two wings and favoured the use of ultrasonic frequencies (Montealegre‐Z, ; Gu et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…As demonstrated by Policha et al (2016) (Morris & Mason, 1995). By changing the material properties of the chamber (photopolymer resin in the 3D model, instead of insect cuticle), Jonsson et al (2017) showed that the morphology of the structure alone is responsible for the amplification of sound. Surface texture can also be modeled well by 3D printing.…”
Section: Biomechanicsmentioning
confidence: 97%
“…In the Neotropical buch‐cricket ( Acanthacara acuta ), the sound produced by the wings is amplified by an unusual extension of the pronotum (the dorsal covering of the thorax), which forms a chamber over the wings. To explore the function of this chamber, 3D printed models have been used to replicate the chamber (Jonsson et al ), which is hypothesized to work as a Helmholtz resonator (Morris & Mason, ). By changing the material properties of the chamber (photopolymer resin in the 3D model, instead of insect cuticle), Jonsson et al () showed that the morphology of the structure alone is responsible for the amplification of sound.…”
Section: Evolutionmentioning
confidence: 99%
See 1 more Smart Citation